2011
DOI: 10.1088/0004-6256/141/3/80
|View full text |Cite
|
Sign up to set email alerts
|

Iras 17423–1755 (Hen 3–1475) Revisited: An O-Rich High-Mass Post-Asymptotic Giant Branch Star

Abstract: The high-resolution (R ∼ 600) Spitzer/IRS spectrum of the bipolar protoplanetary nebula (PN) IRAS 17423−1755 is presented in order to clarify the dominant chemistry (C-rich versus O-rich) of its circumstellar envelope as well as to constrain its evolutionary stage. The high-quality Spitzer/IRS spectrum shows weak 9.7 μm absorption from amorphous silicates. This confirms for the first time the O-rich nature of IRAS 17423−1755 in contradiction to a previous C-rich classification, which was based on the wrong ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…An HST image of IRAS 17393−2727 shows a highly collimated bipolar outflow, as well as a dark lane that completely obscures the central source (Manteiga et al 2011). The infrared spectrum of this source shows bright [Ne II] nebular emission, strongly suggesting that the ionization of its central region has already started (García-Hernández et al 2007).…”
Section: Iras 17393−2727mentioning
confidence: 97%
“…An HST image of IRAS 17393−2727 shows a highly collimated bipolar outflow, as well as a dark lane that completely obscures the central source (Manteiga et al 2011). The infrared spectrum of this source shows bright [Ne II] nebular emission, strongly suggesting that the ionization of its central region has already started (García-Hernández et al 2007).…”
Section: Iras 17393−2727mentioning
confidence: 97%
“…4.8. IRAS 17393−2727 (OH 0.9+1.3) This source shows a bipolar morphology in the optical(Manteiga et al 2011), and its IR colors suggest that the central star is strongly obscured(Ramos-Larios et al 2012). The presence of bright [Ne II] emission indicates that it is a planetary nebula(García-Hernández et al 2007).…”
mentioning
confidence: 99%
“…Smolders et al (2012) have used silicates and gehlenite to fit the observed 10 and 18µm silicate features and have also noted that grain models with a component of SiC may not fit the observed silicate features to the M-type stars. The IRAS 17423-1755 is an O-rich AGB star and it too does not fit well with grain models with SiC inclusion (see more on this AGB star in Manteiga et al (2011)).…”
Section: Discussionmentioning
confidence: 97%
“…We have also used the data from the Infrared Spectrograph IRS (Houck et al (2004)); on board the Spitzer Space Telescope, Werner et al (2004) and extracted the spectrum of four M-type and AGB stars using the Cornell Atlas of Spitzer/IRS Sources (CASSIS) extraction procedure (Lebouteiller et al (2015)). Figure 10 shows model fits with observed Spitzer data in the spectral range of 8-13µm for Mtype stars and one AGB star (see Manteiga et al (2011)). It is seen that the composite grain models or porous silicate grain models do not fit the observed Spitzer fluxes satisfactorily.…”
Section: Ir Emission From Dust and Comparison With Observed Datamentioning
confidence: 99%